Theoretical of the precondition of construction of the concept of continuous ecological education - R V Oparin (Peoples' Friendship University of Russia (RUDN University), 2010)
In given article the essence, structure, principles, the maintenance of the concept of continuous ecological education in Republic Altai are considered. The basic directions of realization of the concept and expected results are shown.